Thank You to Our 2023 Reviewers - Kelly K. Caylor; Amir AghaKouchak; Carole Dalin; Kirsten deBeurs; Gonéri Le Cozannet; Noah S. Diffenbaugh; Dabo Guan; Robert E. Kopp; Jesse Kroll; Ashok Mishra; Vimal Mishra; Patrick M. Reed; et al. (Earth's Future, 2024)
Abstract On behalf of the journal, AGU, and the scientific community, we, the editors of Earth's Future, are delighted to publish the names of the 817 peer reviewers who provided 1,242 reviews for our journal in 2023 (italicized names have contributed three or more reviews). Your diligent efforts to provide timely comments on our submissions have significantly improved the manuscripts and elevated the scientific rigor of future research. As a unique transdisciplinary journal, Earth's Future delves into the state of the planet and its inhabitants, sustainable and resilient societies, the science of the Anthropocene, and predictions of our shared future through research articles, reviews, and commentaries. In the face of observed and anticipated global environmental and climatic changes, the need for high‐quality scientific theories, assessments, and projections about the future of our planet has never been more pressing. To safeguard research integrity in this crucial area, we rely on our reviewers' expertise and selfless cooperation. We extend our heartfelt thanks to each of the individuals listed below for their contributions to our journal and the broader scientific discourse. Your dedication is immensely appreciated.